THE EFFECT OF ORGANIZING TRAINING PROGRAMS AND HUMAN RESOURCE DEVELOPMENT ON THE PERFORMANCE OF THE PARI CITY VILLAGE COMMUNITY, PANTAI CERMIN DISTRICT, SERDANG BEDAGAI REGENCY - Rizky, Muhammad Chaerul; Ardian, Noni; Putra, Nusa Ekasyah (Proceeding International Conference of Science Technology and Social Humanities, 2022)
This  research was conducted to find out  and understand how  the influence of the implementation of the Training and Human Resource Development program on Community Performance. This research was conducted in Pari City Village, Pantai Cermin District, Serdang Bedagai Regency. The research method used in this study is descriptive quantitative with multiple linear regression analysis. The sample used in this study was 30 respondents who were residents of Pari City Village. The results showed that partially  and simultaneously the variables of HR Training and Development had a positive and significant effect on Community Performance. The varied contribution of training and human resource development to community performance was 45.5%.